2021
DOI: 10.3390/biom11101408
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Astrocytic Histamine N-Methyltransferase as a Possible Target for the Treatment of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) represents the principal cause of dementia among the elderly. Great efforts have been established to understand the physiopathology of AD. Changes in neurotransmitter systems in patients with AD, including cholinergic, GABAergic, serotoninergic, noradrenergic, and histaminergic changes have been reported. Interestingly, changes in the histaminergic system have been related to cognitive impairment in AD patients. The principal pathological changes in the brains of AD patients, related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 179 publications
(211 reference statements)
0
9
0
Order By: Relevance
“…From rigid docking studies, it is possible to observe that selected drugs and reference HNMT inhibitor (metoprine) showed interactions with amino acids located in the histamine-binding domain, and particularly with Tyr-146, Tyr-147, Val-173, Trp-179, Trp-183, Cys-196, and Tyr-198, which have been known to play important roles in HNMT inhibition [ 8 ]. The structures of selected compounds are showed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From rigid docking studies, it is possible to observe that selected drugs and reference HNMT inhibitor (metoprine) showed interactions with amino acids located in the histamine-binding domain, and particularly with Tyr-146, Tyr-147, Val-173, Trp-179, Trp-183, Cys-196, and Tyr-198, which have been known to play important roles in HNMT inhibition [ 8 ]. The structures of selected compounds are showed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Initially, the re-docking of metoprine to the binding site of HNMT enzyme was carried out to validate that the reference ligand was docked to the HNMT receptor in the way in which it was experimentally observed. The resulting complex showed ten significant amino acids involved in the interactions: Tyr-15, Glu-28, Tyr-146, Tyr-147, Val-173, Trp-179, Trp-183, Cys-196, and Tyr-198, which are important for HNMT recognition [ 8 ] ( Figure S1C in Supplementary Materials ). The RMSD between the docked and the crystal structure of metoprine was only 0.98 Å (less than 1 Å), which is satisfactory.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, depending on the receptors it acts on, histamine can also have pro-inflammatory properties by promoting the production of various chemokines ( Kim et al., 2022 ). It was reported that histamine may be associated with neuroinflammatory diseases, which may exacerbate the severity of AD ( Flores-Clemente et al., 2021 ). The concentration and localization of histamine receptors in the central or systemic regions have a broad impact on the occurrence of neuroinflammation, and regulating the gut microbiota to cause changes in histamine has become a possible route for treating inflammation ( Carthy and Ellender, 2021 ).…”
Section: Signaling Mechanisms Of Microbiota Gut Brain Axis Communicationmentioning
confidence: 99%